Limping in twenty years old male A Case Report - Al- Iedani, Mohammed S.; Majeed, Ghadeer H.; Al-Assadi, Tarek K. , (AL-Kindy College Medical Journal, 2014)
Background: Osteoid osteoma(OO) is a relatively common benign skeletal neoplasm of unknown etiology that is composed of osteoid and woven bone, usually seen in adolescent and young males Although, the clinical, radiological and scintigraphic features of OO have been well described, these features may be misleading or altered in the cases of lesser trochanter of the femur which is relatively uncommon location for OO with a few number of cases reported up to date.Case Presentation: We report a case of a 20-year-old man who presented with painful limpThe pain had begun six months earlier and was made worse by walking and by exercise., with normal initial X-rays .The diagnosis was made after six months when typical Computed tomography, magnetic resonance imaging findings appeared , showing the nidus.Treatment: Acompleteen block resection accomplished successfully and the whole tumor with lesser trochanter of the femur in one mass was removed.Outcome and Follow-up: the post-operative period was uneventful. The pathological examination is consistent withosteoid osteoma. The patient was asymptomatic at one year follow up.Conclusions: lesser trochanter OO can mimic lots of pathologic entities related to the affected area, and presents a diagnostic challenge and cause a delay in the diagnosis. The delays in the diagnosis and treatment can be avoided with a high index of suspicion. Treatment should be individualized according to the surgeon’s preference and the characteristics of the case.Key words: Osteoid osteoma OO, lesser trochanter, enblock excision